2024
DOI: 10.3389/fonc.2024.1366223
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of m6A modification in ovarian cancer: progression, drug resistance, and therapeutic prospects

Shahil Alam,
Pankaj Kumar Giri

Abstract: Ovarian Cancer (OC) ranks as a prominent contributor to mortality among female reproductive system associated cancers, particularly the prevalent subtype epithelial Ovarian Cancer (EOC). Despite advancements in treatment modalities, the prognosis for OC patients remains grim due to limitation of current therapeutic methodology such as high cytotoxicity of chemotherapeutic agents and tumor relapse making existing chemotherapy ineffective. Recognizing the limitations of a broad-spectrum approach to treating OC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…Finally, Chitcholtan and colleagues evaluated the anticancer effects of resveratrol, a natural compound with several beneficial effects [22][23][24][25], on ovarian cancer cell lines, i.e., OVCAR-8 and SKOV-3, grown on the chorioallantoic membrane (CAM) of chicken embryos. The authors found that resveratrol significantly reduced angiogenic activities, pNF-κB levels, and SLUG protein levels, suggesting that this compound may have the potential to impact the behavior of ovarian cancer progression.…”
mentioning
confidence: 99%
“…Finally, Chitcholtan and colleagues evaluated the anticancer effects of resveratrol, a natural compound with several beneficial effects [22][23][24][25], on ovarian cancer cell lines, i.e., OVCAR-8 and SKOV-3, grown on the chorioallantoic membrane (CAM) of chicken embryos. The authors found that resveratrol significantly reduced angiogenic activities, pNF-κB levels, and SLUG protein levels, suggesting that this compound may have the potential to impact the behavior of ovarian cancer progression.…”
mentioning
confidence: 99%